2021
DOI: 10.3389/fphar.2021.755396
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction and Bioactivity Evaluation of Chemical Ingredients Against Influenza A Virus From Isatis tinctoria L

Abstract: Influenza A virus (IAV) is one of the major causes of seasonal endemic diseases and unpredictable periodic pandemics. Due to the high mutation rate and drug resistance, it poses a persistent threat and challenge to public health. Isatis tinctoria L. (Banlangen, BLG), a traditional herbal medicine widely used in Asian countries, has been reported to possess strong efficacy on respiratory viruses, including IAV. However, its effective anti-IAV components and the mechanism of actions (MOAs) are not yet fully eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…[ 30 ] Blocking of the MAPK pathway is correlated with inhibited HSC proliferation. [ 56–58 ] Moreover, we added MAPK activator into Tβ4‐overexpressing TGF‐β1‐induced LX‐2 cells and observed elevated cell proliferation and migration. Tβ4 can suppress interleukin‐1β‐elicited HSC‐LX2 cell proliferation by regulating the NF‐κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Blocking of the MAPK pathway is correlated with inhibited HSC proliferation. [ 56–58 ] Moreover, we added MAPK activator into Tβ4‐overexpressing TGF‐β1‐induced LX‐2 cells and observed elevated cell proliferation and migration. Tβ4 can suppress interleukin‐1β‐elicited HSC‐LX2 cell proliferation by regulating the NF‐κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Systems pharmacology had been recentely developed in TMC studies, it provided a network perspective to explore the relationship between components and targets [ 21 ]. It has been shown that systems pharmacology gave an effective approaches to identify the bioactive compounds, predict the corresponding targets and elucidate the molecular mechanisms about how does TCM work on different diseases [ 22 , 23 ]. For instance, by using this strategy, it uncovered the mechanism of Huanglian-Wuzhuyu herb pair in treating nonalcoholic steatohepatitis and predicted active ingredients, it also explained mechanism of Lianhuaqingwen capsule in treating COVID-19 [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structure-based approaches such as molecular docking are always encumbered by the computing speed and the resolution of crystal structures [ 23 ]. Besides, network approach based on system pharmacology, which comprehensively considers the information of drug-target network and disease-related genes, provides new insights into the identification of active ingredients against disease [ 26 28 ]. Nevertheless, as the object of this study is rare ginsenosides, most of which remain nearly unknown for the information of interacted targets.…”
Section: Introductionmentioning
confidence: 99%